The circuits of healthcare: Understanding healthcare seeking behaviour-A qualitative study with tuberculosis patients in Lisbon, Portugal. - Rafaela M Ribeiro; Philip J Havik; Isabel Craveiro (PLoS ONE, 2021)
Background Understanding health delivery service from a patient´s perspective, including factors influencing healthcare seeking behaviour, is crucial when treating diseases, particularly infectious ones, like tuberculosis. This study aims to trace and contextualise the trajectories patients pursued towards diagnosis and treatment, while discussing key factors associated with treatment delays. Tuberculosis patients' pathways may serve as indicator of the difficulties the more vulnerable sections of society experience in obtaining adequate care. Methods We conducted 27 semi-structured interviews with tuberculosis patients attending a treatment centre in a suburban area of Lisbon. We invited nationals and migrant patients in active treatment to participate by sharing their illness experiences since the onset of symptoms until the present. The Health Belief Model was used as a reference framework to consolidate the qualitative findings. Results By inductive analysis of all interviews, we categorised participants' healthcare seeking behaviour into 4 main types, related to the time participants took to actively search for healthcare (patient delay) and time the health system spent to diagnose and initiate treatment (health system delay). Each type of healthcare seeking behaviour identified (inhibited, timely, prolonged, and absent) expressed a mindset influencing the way participants sought healthcare. The emergency room was the main entry point where diagnostic care cascade was initiated. Primary Health Care was underused by participants. Conclusions The findings support that healthcare seeking behaviour is not homogeneous and influences diagnostic delays. If diagnostic delays are to be reduced, the identification of behavioural patterns should be considered when designing measures to improve health services' delivery. Healthcare professionals should be sensitised and perform continuous capacity development training to deal with patients´ needs. Inhibited and prolonged healthcare seeking behaviour contributes significantly to diagnostic delays. These behaviours should be detected and reverted. Timely responses, from patients and the healthcare system, should be promoted.